Molecular Docking, Synthesis and In Vitro Antiplasmodium Assay of Monoketone Curcumin Analogous from 2-Chlorobenzaldehyde - Mustika, Chessy Rima; Astuti, Endang; Mardjan, Muhammad Idham Darussalam (Universitas Gadjah Mada, 2024)
This research aimed to develop new curcumin analogous as antiplasmodium candidates. Six curcumin analogous (1-6) were proposed and docked against three Plasmodium falciparum receptors, namely PfENR, PfLDH, and PfATP6. The docking studies were carried out to predict the interaction among the compounds and receptors as well as their binding affinity. Three curcumin analogous (3, 4, and 6), which displayed specific interactions with the target receptors and possessed the lowest binding affinity were further proceeded to synthesis and in vitro antiplasmodium assay. Synthesis of the analogous 3, 4, and 6 was carried out from 2-chlorobenzadehyde via aldol condensation reaction and the products were obtained in good yields. Their in vitro antiplasmodium activities were then evaluated against P. falciparum FCR3 and 3D7 strains. The results showed that analogous 3, 4, and 6 were active against both strains with low levels of resistance. The in silico evaluation of the physicochemical and pharmacokinetic parameters showed that curcumin analogous displayed a better ADMET profile than curcumin, demonstrating the great potential of the developed curcumin analogous as antiplasmodium candidates.